Synthesis of meso-arylsubstituted lypoporphyrins to design nanosized lipid assembles - I. N. Fedulova; N. V. Novikov; O. A. Ugolnikova; N. A. Bragina; A. F. Mironov (Тонкие химические технологии)
Synthesis of meso-arylsubstituted porphyrins with hydrophobic long chain groups by using the dipyrromethanes method and monopyrrolic condensation is described. Data lypoporphyrins possess liquid crystalline properties and will be used to design supramolecular nanosized lipid assembles